Designing Groups for Judgmental Decisions - Stumpf, Stephen A.; Zand, Dale E.; Freedman, Richard (Academy of Management Review, 1979)
To design effective judgmental decision-making groups, one must consider: (1) decision criteria, (2) situation characteristics, (3) membership, and (4) how the group functions. This paper proposes a model for synthesizing these elements. First, interactions among the elements are formulated as design propositions. Then the propositions are integrated in a decision tree to guide practitioners and researchers.